EFEK ADAPTOGENIK EKSTRAK ETANOL KULIT BUAH MANGGIS (Garcinia mangostana L.) PADA MENCIT (Mus musculus) MENGGUNAKAN METODE SWIMMING ENDURANCE TEST - Abdul Wahid Jamaluddin; A. Magfira Satya Apada (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Adaptogenic activity was related to antioxidant activity which can reduce the number of free radicals, which in turn will reduce stress and improve body balance. Mangosteen rind (Garcinia mangostana L.) with a large antioxidant content promises to be Adaptogen. This study aims to examine the Adaptogenic effects of Ethanol Extract of mangosteen peel (Garcinia Mangostana L.) Using the Swimming Endurance Test (SET) in Mice. Simplicia of Mangosteen Fruit extracted by maceration using 96% ethanol, then tested its Adaptogen activity based on swimming endurance test. The group consisted of negative control (NaCMC 1%), positive control (Vit C. 100 mg / kg BB) and 3 groups treatment of ethanol extract of mangosteen peel ranging from 100, 200 and 400 mg / kg BB where all groups were given oral 1x1 oral administration for 7 days and on the 8th day, a SET test were performed. After that, data analysis was performed statistically. The results showed that the ethanol extract of mangosteen peel had the ability to be Adaptogenic where mice swimming in all groups given mangosteen peel extract was longer than the negative group with a significant difference (p <0.05). Ethanol extract of mangosteen peel showed a strong adaptogenic antistress effect in mice based on increased swimming time ability of mice.